Rancang Bangun Filter Harmonik Untuk Perbaikan Kualitas Daya Pada Pembangkit Listrik Tenaga Surya 320 WP - Anggoro Arso Pambudi; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
With the progress of industry, power electronic equipment is widely used in power system, it has produced serious harmonic distorsion. It goes without saying that harmonic analysis is a very important subject in power system. The influence of harmonics dominant because it is permanent. This harmonic influence spread to energy systems, energy devices, and influential to the energy source. For that it is necessary a tool that is able to overcome these problems so that the electric energy services are not compromised and the reliability was not reduced. This study how to harmonic analysis, total harmonic distrosion, and identifying the inverter at a solar power plant 320WP in accordance with the IEEE 519-2014.Keywords: harmonic, THD, inverter, solar power plant 320WP, IEEE